The Pictorial Fit-Frail Scale: developing a visual scale to assess frailty - Theou, Olga; Andrew, Melissa; Ahip, Sally Suriani; Squires, Emma; McGarrigle, Lisa; Blodgett, Joanna M.; Goldstein, Judah; Hominick, Kathryn; Godin, Judith; Hougan, Glen; Armstrong, Joshua J.; Wallace, Lindsay; et al. (Canadian Geriatrics Society, 2019)
Background: Standardized frailty assessments are needed for early identification and treatment. We aimed to develop a frailty scale using visual images, the Pictorial Fit-Frail Scale (PFFS), and to examine its feasibility and content validity. Methods: In Phase 1, a multidisciplinary team identified domains for measurement, operationalized impairment levels, and re-viewed visual languages for the scale. In Phase 2, feedback was sought from health professionals and the general public. In Phase 3, 366 participants completed preliminary testing on the revised draft, including 162 UK paramedics, and rated the scale on feasibility and usability. In Phase 4, following translation into Malay, the final prototype was tested in 95 participants in Peninsular Malaysia and Borneo. Results: The final scale incorporated 14 domains, each conceptualized with 3–6 response levels. All domains were rated as “understood well” by most participants (range 64–94%). Percentage agreement with positive statements regarding appearance, feasibility, and usefulness ranged from 66% to 95%. Overall feedback from health-care professionals supported its content validity. Conclusions: The PFFS is comprehensive, feasible, and appears generalizable across countries, and has face and content validity. Investigation into the reliability and predictive validity of the scale is currently underway.